2019
DOI: 10.1186/s12917-019-1978-6
|View full text |Cite
|
Sign up to set email alerts
|

A survey of antimicrobial use practices of Tennessee beef producers

Abstract: Background Inappropriate antimicrobial use (AMU) is a key modifiable factor that leads to the development of antimicrobial resistance (AMR). The objectives of this study were to determine the following among Tennessee beef cattle producers: (1) the opinions on factors driving AMU (2) opinions on alternatives to antimicrobials, (3) the knowledge and perceptions regarding AMU and AMR, and (4) the preferred avenues for receiving information on prudent AMU. A survey questionnaire was made available to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Globally, elevating farmer knowledge through education was found to influence AMU and encourage appropriate practices on farms across all sectors, countries and regions. 20 , 26 , 32 , 39 , 44 , 45 , 48 , 54–58 Moreover, it is important to note that farmers were receptive to interventions that improved knowledge and awareness. For example, in the UK, Italy and Germany, farmers were interested in strengthening their knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Globally, elevating farmer knowledge through education was found to influence AMU and encourage appropriate practices on farms across all sectors, countries and regions. 20 , 26 , 32 , 39 , 44 , 45 , 48 , 54–58 Moreover, it is important to note that farmers were receptive to interventions that improved knowledge and awareness. For example, in the UK, Italy and Germany, farmers were interested in strengthening their knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, farmers described an emotive bond to livestock and therefore felt a responsibility to maintain herd health. 15 , 17 , 38 , 54 , 55 , 81–83 Similarly, numerous UK studies indicated that vets felt a sense of responsibility in ensuring animal welfare and alleviating animal suffering. 17 , 43 , 64 , 74 Norwegian farmers indicated that maintaining herd health without depending on antimicrobials gave farmers a sense of personal satisfaction and control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations